Design and research for the water low-pressure large-flow pilot-operated solenoid valve - Liu, Lei (Strojniški vestnik, 2014)
The basic requirements of the valve-control coupling for control valves are quick response, high flow capacity, and anti-blocking ability. In this article, a pure water hydraulic test-bed is built, and the pressure distribution characteristics between the throttle nozzle and the pilot valve, as well as the flow characteristics in the throttle orifice are researched. Following that, the water medium low pressure large-flow pilot operated solenoid valve is designed. The influences of throttle nozzles' diameter and other parameters on the dynamic and static characteristics of the valve are analysed via AMESim simulation software. The optimized combination of parameters of the solenoid valve group is determined. The experiment results show that the normal working pressure drop of the designed solenoid valve group is approximately 0.07 MPa, the opening time is 0.3 to 0.4 s, the closing time is approximately 1 s; it possesses better low pressure characteristics and rapid response characteristic, which can satisfy the requirements of valve-control coupling.
Keywords: dušilna odprtina; nizek tlak; pilotni elektromagnetni ventil; velik pretok; voda kot medij; zgradba glavnega ventila